The combined use of Er,Cr:YSGG laser and fluoride to prevent root dentin demineralization - Vinícius Rangel GERALDO-MARTINS; Cesar Penazzo LEPRI; Juliana Jendiroba FARAONI-ROMANO; Regina Guenka PALMA-DIBB (Journal of Applied Oral Science, 2014)
The use of erbium lasers to prevent caries in enamel has shown positive results. However, it is not known if Er,Cr:YSGG laser can also be used to increase acid resistance of root dentine, which is another dental tissue susceptible to the action of cariogenic bacteria. Objective: To analyze the effects of the Er,Cr:YSGG laser (λ=2.78 μm, 20 Hz) irradiation associated with 2% neutral sodium fluoride (NaF) to prevent root dentin demineralization. Material and Methods: One hundred human root dentin samples were divided into 10 groups (G) and treated as follows: G1: no treatment; G2: NaF; G3: laser (4.64 J/cm2) with water cooling (WC=5.4 mL/min); G4: laser (4.64 J/cm2) without WC; G5: laser (8.92 J/cm2) with WC; G6: laser (8.92 J/cm2) without WC; G7: laser (4.64 J/cm2) with WC and NaF; G8: laser (4.64 J/cm2) without WC and NaF; G9: laser (8.92 J/cm2) with WC and NaF; G10: laser (8.92 J/cm2) without WC and NaF. The NaF gel was applied alone or after 4 min of irradiation. After 14 days of acid challenge, the samples were sectioned and the Knoop microhardness (KHN) test was done at different depths (30, 60, 90 and 120 μm) from the outer dentin surface. Data were analyzed by one-way ANOVA and Fisher’s test (α=5%). Results: The results showed that G8 and G10 presented higher KHN than the G1 for the depths of 30 and 60 μm, indicating an increase of the acid resistance of the dentin in up to 35% (p<0.05). Conclusions: The use of Er,Cr:YSGG laser irradiation at 4.64 J/ cm2 and 8.92 J/cm2 without water cooling and associated with 2% NaF can increase the acid resistance of human root dentin.